DNA computation - Wang, Qi Wen. (2009)
Since Leonard Adleman successfully proposed and demonstrated the possibilities of DNA computation in 1994, many researchers has contributed to the field of DNA computation. The project aims to develop 4 different types of DNA computational algorithms corresponding to 4 different types of graphical combinatorial problems based on the latest research – shortest path problem with equivalent and inequivalent edge length, shortest spanning tree and assignment problem. Each developed DNA computational algorithm comes along with independent analysis section which explains the working principle lying behind the developed algorithm. In addition, the project also demonstrates the existing silicon-based computing algorithm as well as developed DNA computational algorithm in a specified case study. The aim is to compare the two different algorithms in terms of complexity, performance and efficiency.